Treatment of Miller Class I Gingival Recession with Using Nonpedicle Adipose Tissue after Bichectomy Surgical Technique: A Case Report - Carmen Lucia Mueller Storrer; Leonardo Luiz Muller; Janes Francio Pissaia; Carla Frehner Andrade; Claudia Roberta Tenório Trevisani; Tatiana Miranda Deliberador (Hindawi Limited, 2019)
Gingival recession is an oral health problem that affects a large part of the population. Several treatments are suggested in the current literature; among them is the use of buccal fat pad grafting. The objective of this case report is to describe the treatment of a Miller Class I gingival recession using a nonpedicled buccal fat pad graft immediately after performing the surgery for buccal fat pad removal (bichectomy technique). First, bilateral surgical removal of the buccal fat pad was performed with the main objective of eliminating oral mucosa biting. The recipient site was prepared to receive a portion of the fat pad that was cut and macerated in a size that was sufficient to cover the recession. The patient was followed up at 15, 30, 60, and 365 days postsurgery, and the results showed an elimination of the oral mucosa biting and complete coverage of the gingival recession. It was concluded that the nonpedicled buccal fat pad graft is another option for the treatment of Miller Class I recessions.